Staphylococcal scalded skin syndrome in a premature newborn caused by methicillin-resistant Staphylococcus aureus: case report - Hörner, Andreas; Hörner, Rosmari; Salla, Adenilde; Nunes, Melise Silveira; Garzon, Litiérri Razia; Rampelotto, Roberta Filipini; Martini, Rosiéli; Santos, Silvana Oliveira dos; Gindri, Lívia; Rodrigues, Mônica de Abreu; Giacomolli, Cláudia (São Paulo Medical Journal, 2015)
CONTEXT: Staphylococcal scalded skin syndrome is an exfoliative skin disease. Reports of this syndrome in newborns caused by methicillin-resistant Staphylococcus aureus are rare but, when present, rapid diag-nosis and treatment is required in order to decrease morbidity and mortality. CASE REPORT: A premature newly born girl weighing 1,520 g, born with a gestational age of 29 weeks and 4 days, developed staphylococcal scalded skin syndrome on the fifth day of life. Cultures on blood samples collected on the first and fourth days were negative, but Pseudomonas aeruginosa and Entero-coccus sp. (vancomycin-sensitive) developed in blood cultures performed on the day of death (seventh day), and Pseudomonas aeruginosa and Serratia marcescens were identified in cultures on nasopharyngeal, buttock and abdominal secretions. In addition to these two Gram-negative bacilli, methicillin-resistant Staphylococcus aureus was isolated in a culture on the umbilical stump (seventh day). The diagnosis of staphylococcal scalded skin syndrome was based on clinical criteria.